Increased nociceptin/orphanin FQ plasma levels in hepatocellular carcinoma - Szalay, Ferenc (World J Gastroenterol, 2004)
AIM: The heptadecapeptide nociceptin alias orphanin FQ is the endogenous agonist of opioid receptor-like1 receptor. It is involved in modulation of pain and cognition. High blood level was reported in patients with acute and chronic pain, and in Wilson disease. An accidental observation led us to investigate nociceptin in hepatocellular carcinoma METHODS: Plasma nociceptin level was measured by radioimmunoassay, aprotinin was used as protease inhibitor. Hepatocellular carcinoma was diagnosed by laboratory, ultrasound, other imaging, and confirmed by fine needle biopsy. Results were compared to healthy controls and patients with other chronic liver diseases. RESULTS: Although nociceptin levels were elevated in patients with Wilson disease (14.0 ± 2.7 pg/mL, n = 26), primary biliary cirrhosis (12.1 ± 3.2 pg/mL, n = 21) and liver cirrhosis (12.8 ± 4.0 pg/mL, n = 15) compared to the healthy controls (9.2 ± 1.8 pg/mL, n = 29, P < 0.001 for each), in patients with hepatocellular carcinoma a ten-fold increase was found (105.9 ± 14.4 pg/mL, n = 29, P < 0.0001). High plasma levels were found in each hepatocellular carcinoma patient including those with normal alpha fetoprotein and those with pain (104.9 ± 14.9 pg/mL, n = 12) and without (107.7 ± 14.5 pg/mL, n = 6). CONCLUSION: A very high nociceptin plasma level seems to be an indicator for hepatocellular carcinoma. Further research is needed to clarify the mechanism and clinical significance of this novel finding.